Cartoon Crazys - Comic Book Heroes - Sparber, Isidore; Fleischer, Dave; Kneitel, Seymour; Gillett, Burt; Palmer, Tom (Winstar, 2000)
As the title suggests, many of the characters in this offbeat collection began in comic books, but not all: Felix the Cat and Betty Boop debuted in animated films, and Popeye, Little Nemo, and the Toonerville folk appeared in newspaper strips long before comic books existed. The most striking films are the two Superman shorts. In "The Underground World" (1943), a race of hawk-men threaten to dip Lois and a scientist into a vat of boiling wax. "Electronic Earthquake" (1942) features an Native American villain who insists that Manhattan Island still belongs to his people. The oddest entries in the collection are an example of "Do Do, the Kid from Outer Space," a '60s British series told in doggerel rhyme, and a chunk of "Tobor the 8th Man", an extremely limited Japanese superhero adventure, also from the '60s. Most of the rest of the cartoons represent the work of animation's B studios. [www.amazon.com]